A bibliometric analysis of acute myocardial infarction in women from 2000 to 2022 - Xu, Ming; Yang, Fupeng; Shen, Bin; Wang, Jiamei; Niu, Wenhao; Chen, Hui; Li, Na; Chen, Wei; Wang, Qinqin; HE, Zhiqing; Ding, Ru (Frontiers in Cardiovascular Medicine, 2023)
Background Plenty of publications had been written in the last several decades on acute myocardial infarction (AMI) in women. However, there are few bibliometric analyses in such field. In order to solve this problem, we attempted to examine the knowledge structure and development of research about AMI in women based on analysis of related publications. Method The Web of Science Core Collection was used to extract all publications regarding AMI in women, ranging from January 2000 to August 2022. Bibliometric analysis was performed using VOSviewer, Cite Space, and an online bibliometric analysis platform. Results A total of 14,853 publications related to AMI in women were identified from 2000 to 2022. Over the past 20 years, the United States had published the most articles in international research and participated in international cooperation the most frequently. The primary research institutions were Harvard University and University of Toronto. Circulation was the most cited journal and had an incontrovertible academic impact. 67,848 authors were identiﬁed, among which Harlan M Krumholz had the most signiﬁcant number of articles and Thygesen K was co-cited most often. And the most common keywords included risk factors, disease, prognosis, mortality, criteria and algorithm. Conclusion The research hotspots and trends of AMI in women were identified and explored using bibliometric and visual methods. Researches about AMI in women are ﬂourishing. Criteria and algorithms might be the focus of research in the near future, which deserved great attentions.